Catálogo dos livros de horas da Biblioteca Nacional do Brasil - Faillace, Vera Lúcia Miranda (2009)
The objective of the present monograph is to identify the books of hours pertaining to the National Library of Brazil, aiming at the production of a catalogue. The collection comprises nine illuminated manuscript books; however, only the items produced in the second half of the 15th century are identified in this work. The provenance of four of these books is the Portuguese Royal Library – Casa do Infantado, which was transferred to Brazil in 1808, together with Portugal’s Royal family, thus becoming the core of the Brazilian National Library. The first part of the monograph includes theoretical considerations and situates the period in which the books were created, also putting in relief their importance, both to medieval society and to the evolution of devotions. A brief history of the National Library and information related of the catalogue’s construction are also presented. The second part of the monograph presents the catalogue itself, where the books are described according to intenational rules, enabling access, diffusion and data interchanging, thus valuing and promoting the preservation of these cultural and patrimonial assets.